Diseño de un plan de sucesión basado en un modelo de competencias para el personal clave de una empresa constructora - Ayala Treviño, Jesica Abigail (2013)
Based on the contributions made by the various authors and subject matter experts and recognizing the importance for organizations to have a strategic human resource planning that takes into consideration the Succession Planning, this research aims to solve one of the major problems affecting a construction company in Monterrey, Nuevo León, by not having a succession plan for the management of human talent, allowing it to detect and retain staff with the skills and abilities needed to fill a certain key position in each of the directions that make it up.